2009
DOI: 10.1093/molbev/msp180
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Dating of Novel Haplotypes of HERV-K 113 and HERV-K 115 Indicate These Proviruses Originated in Africa before Homo sapiens

Abstract: The human genome, human endogenous retroviruses (HERV), of which HERV-K113 and HERV-K115 are the only known full-length proviruses that are insertionally polymorphic. Although a handful of previously published papers have documented their prevalence in the global population; to date, there has been no report on their prevalence in the United States population. Here, we studied the geographic distribution of K113 and K115 among 156 HIV-1+ subjects from the United States, including African Americans, Hispanics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 46 publications
2
52
1
Order By: Relevance
“…Recently, however, recognition that the HERV-K108 glycoprotein has residual functional activity plus the in silico generation of consensus prototypic HERV-K(HML-2) sequences have added considerably to our basic understanding of the virus and its proteins (20,21,39). The data presented here describe a strategy to overcome the poor expression and document efforts to reconstitute a HERV-K(HML-2) Env protein coded for by the HERV-K113 element that originally entered the human germ line as an infectious retrovirus more than 800,000 years ago (33,54). This provirus is one of the most studied elements.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, however, recognition that the HERV-K108 glycoprotein has residual functional activity plus the in silico generation of consensus prototypic HERV-K(HML-2) sequences have added considerably to our basic understanding of the virus and its proteins (20,21,39). The data presented here describe a strategy to overcome the poor expression and document efforts to reconstitute a HERV-K(HML-2) Env protein coded for by the HERV-K113 element that originally entered the human germ line as an infectious retrovirus more than 800,000 years ago (33,54). This provirus is one of the most studied elements.…”
Section: Discussionmentioning
confidence: 99%
“…K109 and K113, also likely candidates for replication competence (76,77,79,80), had RPKM values below our limit of detection or were not able to be analyzed in this study, respectively. K113 is the most recent germ line integration known (10,76), with an allele frequency of ϳ16% in the population (10,76); thus, it is not yet fixed in the human population. As such, it is possible that K113 is not present in the genome of the PBL donor.…”
Section: Hiv-1 Tat Both Activates and Silences Specific Herv-k (Hml-2)mentioning
confidence: 88%
“…These results suggest that Tat treatment, in addition to activating, also represses HERV-K (HML-2) expression. Interestingly, of these activated proviruses, K108 and K115 (considered among the most likely candidates to remain replication competent in modern humans) (76)(77)(78)(79) are significantly activated by Tat treatment. K109 and K113, also likely candidates for replication competence (76,77,79,80), had RPKM values below our limit of detection or were not able to be analyzed in this study, respectively.…”
Section: Hiv-1 Tat Both Activates and Silences Specific Herv-k (Hml-2)mentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few sequence polymorphisms have been described, partly due to the difficulty in identifying them against the background of closely similar proviruses. Using specific PCR primers spanning 5'LTRs of K115 and K113, Jha et al (45) reported the presence of three single nucleotide polymorphism sites in the K113 5'LTR and four in the K115 5'LTR that together constituted four haplotypes for K113. At present, there is little convincing evidence that any sequence polymorphism of a HERV provides susceptibility to human disease.…”
Section: Effect Of Possible Mechanisms Of Herv Ltr In Cancermentioning
confidence: 99%